The management practice in communitary health units - preview note - Ana Lucia Abrahão (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
Based on the articulation of concepts that makes working with management and subjectivity possible, a rich interpretation phenomenon, this research takes its main references from the Institutional Analysis, the Socioanalysis and the Scientific Administration in a way of improving theory based on live reality. It aims to map in the daily management of basic health units which management processes used in the conduction of the organization find power for the construction of a prevention and decentralization centered assistance model. For such, the qualitative approach will guide this research that intends to take as inquiry field basic health units in the city of Niterói. Bibliographical survey, questionnaire and a field diary will be used as inquiry method. One expects that the produced material will be object of discussion in the units that participate in the study. It is also expected that the research will fortify the health management field and that it will aloud the constitution of a bigger joint space between education and services. A scientific article will also be produced. The esteemed research time is of two years.